Capital availability, small business formation and performance in Barbados, Jamaica and Trinidad : an empirical foray. - Henry, C. Michael (1990)
Posits that small enterprise performance depends on (1) characteristics of the entrepreneur; (2) the degree of access to capital; (3) age of the enterprise; (4) exogenous demand conditions of the industry which includes the enterprise; and (5) the role of government assistance in enterprise performance.